The Influence of E-Participation and Digital Literacy on Trust in E-Government Services: A Study on the People of Mataram City - Rahmad Hidayat; Ridwan Ridwan; Mustamin Mustamin; Abdurrahman Abdurrahman (Universitas Teuku Umar, 2026)
Digital literacy is the ability of individuals to use ICT to access, evaluate, and produce digital content effectively. Digital literacy in Indonesia is still low, affecting citizen participation in digital governance of government. The purpose of this study is to analyze the contribution of E-Participation and Digital Literacy to Trust in E-Government Services in Big Cities in Indonesia, e-participation variables, digital literacy as well as identifying the weakest indicators in citizen digital engagement. This study uses a quantitative approach with a correlational design. The research subjects were 66 randomly selected residents of Mataram City. Data were analyzed using descriptive statistics and multiple linear regression. The results of the study show Based on the results of descriptive analysis, multiple linear regression, ANOVA, and data graphic visualization, this study concludes that E-Participation (X1) and Digital Literacy (X2) contribute significantly to Trust in E-Government Services (Y). Although both have a positive influence, the Digital Literacy variable is proven to have a stronger and statistically significant contribution (p = 0.025) compared to E-Participation (p = 0.096). The coefficient of determination (R² = 0.253) shows that the two variables explain approximately 25.3% of the variability in public trust in e-government, while the remainder is influenced by other factors outside the model.